Non-Invasive Brain Stimulation: Augmenting the Training and Performance Potential in Esports Players - Wei Zhuang; Keyi Yin; Yahua Zi; Yu Liu (Brain Sciences, 2020)
During the last two decades, esports, a highly competitive sporting activity, has gained increasing popularity. Both performance and competition in esports require players to have fine motor skills and physical and cognitive abilities in controlling and manipulating digital activities in a virtual environment. While strategies for building and improving skills and abilities are crucial for successful gaming performance, few effective training approaches exist in the fast-growing area of competitive esports. In this paper, we describe a non-invasive brain stimulation (NIBS) approach and highlight the relevance and potential areas for research while being cognizant of various technical, safety, and ethical issues related to NIBS when applied to esports.